Unpicking the Emperor’s New Clothes: Perceived Attributes of the Captain in Sports Teams - Fransen, Katrien; Cotterill, Stewart T.; Vande Broek, Gert; Boen, Filip (Frontiers in Psychology, 2019)
Much importance has been assigned to the role of the team captain. In this article, we test whether today’s team captains live up to these high expectations. Furthermore, we provide greater insight into the selection procedures leading to a captain’s appointment and assess how this process impacts upon the captain’s perceived leadership qualities. Adopting a mixed methods design, a total of 398 participants (226 players and 172 coaches) listed the attributes of both their current team captain and their ideal captain. Altogether, participants listed 635 attributes for their current team captain and 919 attributes for their ideal team captain. Both inductive and deductive approaches were used to analyze these qualitative data. Furthermore, quantitative data were obtained on the perceived influencers in the captain’s selection process. The results indicated that, although players and coaches expect their team captains to have good motivational and social leadership skills, the selection process is often underpinned by non-leadership factors, such as experience, sport-specific competence, or irrelevant attributes, such as being the daughter of the club president. This discrepancy held for both coaches’ and players’ perspectives, for male and female teams, across sports, and across competition levels. Although coaches were identified as main influencers in the selection process, giving players the deciding vote did not result in captains with better perceived leadership skills. The significant gap between participants’ expectations of the captain and reality highlights the need for implementing a structure of shared leadership. Furthermore, evidence-based leadership development programs are needed to maximize the team’s leadership potential.